Roles of perivascular adipose tissue in the pathogenesis of atherosclerosis ― an update on recent findings - Hara, Tomoya; Sata, Masataka (Frontiers in Physiology, 2025)
Lifestyle-related diseases, such as atherosclerosis and diabetes, are now considered to be a series of diseases caused by chronic inflammation. Adipose tissue is considered to be an endocrine organ that not only plays a role in lipid storage, heat production, and buffering, but also produces physiologically active substances and is involved in chronic inflammation. Perivascular adipose tissue (PVAT) surrounding blood vessels similarly produces inflammatory and anti-inflammatory physiologically active substances that act on blood vessels either directly or via the bloodstream. Epicardial adipose tissue (EAT), which is in direct contact with the coronary arteries inside the pericardium, is thought to have a direct effect on the coronary arteries as well. The presence and inflammatory status of these adipose tissues can be evaluated by imaging tests, and has been shown to be associated with the presence of current cardiovascular disease (CVD) and to be a prognostic factor. It is also expected to become a new diagnostic and therapeutic target for CVD.